Penerapan Model Human Computer Interaction (HCI) Dalam Analisis Sistem Informasi - Prihati, Prihati; Mustafid, Mustafid; Suhartono, Suhartono (Universitas Diponegoro, 2011)
Information system Analysis is very important to do to produce easy, effective, efficient, and proper use system for the user. This research is meant to design and apply information system analysis model with the concept of Human Computer Interaction (HCI), Jacob Nielsen’s usability criteria which are learnability, efficiency, memorability, errors and satisfaction. The model of information system analysis Human Computer Interaction (HCI) with five usability criteria can be used as a standard to analyze how far Human Computer Interaction can be applied into the system so that every weakness will be known and system maintenance can be performed. The application Human Computer Interaction model in analysis of Sistem Administrasi Sekolah (SAS) produce a conclusion that only half of Human Computer Interaction concept applied into SAS Dikmenti DKI Jakarta. SAS is easy to be learned and to remember but SAS is not efficient and not yet have the ability to cope the mistake well. Users are satisfied enough with the result achieved through SAS but the facility provided by SAS is considered not enough to accommodate the need of the users.